2012
DOI: 10.1111/j.1364-3703.2012.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

CaWRKY58, encoding a groupI WRKYtranscription factor ofCapsicum annuum, negatively regulates resistance toRalstonia solanacearuminfection

Abstract: WRKY transcription factors are encoded by large gene families across the plant kingdom. So far, their biological and molecular functions in nonmodel plants, including pepper (Capsicum annuum) and other Solanaceae, remain poorly understood. Here, we report on the functional characterization of a new group I WRKY protein from pepper, termed CaWRKY58. Our data indicate that CaWRKY58 can be localized to the nucleus and can activate the transcription of the reporter β-glucuronidase (GUS) gene driven by the 35S core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 60 publications
2
70
1
Order By: Relevance
“…We found that group I comprised nearly 25% of the total identified CaWRKYs. Of these, only two CaWRKY members have been functionally identified in disease resistance process (CaWRKY13/Ca02g003339 and CaWRKY45/Ca09g001251)5152. Although current studies attribute group I CaWRKYs to disease resistance, our results suggest that group I CaWRKYs play a more important and fundamental role than other groups in reproductive development, especially in ripening of pepper fruit.…”
Section: Discussioncontrasting
confidence: 55%
“…We found that group I comprised nearly 25% of the total identified CaWRKYs. Of these, only two CaWRKY members have been functionally identified in disease resistance process (CaWRKY13/Ca02g003339 and CaWRKY45/Ca09g001251)5152. Although current studies attribute group I CaWRKYs to disease resistance, our results suggest that group I CaWRKYs play a more important and fundamental role than other groups in reproductive development, especially in ripening of pepper fruit.…”
Section: Discussioncontrasting
confidence: 55%
“…Recently, CaWRKY58 was characterized as a negative regulator and classified as a group I WRKY. CaWRKY58 contained five conserved SP clusters but did not have D-domain51. CaWRKY2, another group I member, was isolated as a pathogen-inducible transcription factor and contained D-domain and five SP clusters although functional study of CaWRKY2 was not carried out52.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of candidate priming genes was analyzed using the following primer pairs: 5 ′ -AGCCTGAAATAGAAGAAACGGAGATGGAGATGAGA-3 ′ ( CaTin1- F), 5 ′ - GGAACCAGAATTGGTTACTCATGGCTACCTGAAC-3 ′ ( CaTin1- R), 5 ′ -ACTTGCAATTATGATCCACC-3 ′ ( CaPR1 -F), 5 ′ -ACTCCAGTTACTGCACCATT-3 ′ ( CaPR1 -R), 5 ′ -AACTGGGATTTGAGAACTGCCAGC-3 ′ ( CaPR4 -F), and 5 ′ - ATCCAAGGTACATATAGAGCTTCC-3 ′ ( CaPR4 -R). As a loading control to ensure that equal amounts of RNA were used in each assay, we also analyzed CaActin using the primers 5 ′ - CACTGAAGCACCCTTGAACCC -3 ′ and 5 ′ - GAGACAACACCGCCTGAATAGC -3 ′ (Wang et al, 2013). Relative transcript quantification was calculated using the 2-ΔΔCT method and standard errors of mean values among replicates were calculated using Bio-Rad manager (version 2.1; Bio-Rad CFX Connect).…”
Section: Methodsmentioning
confidence: 99%